Art Chicago 2000 Catalogue. - Fitzpatrick, Robert; Art Chicago Chicago 2000 (Chicago : Thomas Blackman Associates, 2000)
Arneson, Robert ; Bedia, José ; Dickinson, Edwin ; Guston, Philip ; Calle, Sophie ; Bravo, Marta Maria Pérez ; Calvo, Carmen ; Antille, Emmanuelle ; Kraijer, Juul ; Wharton, Margaret ; Munoz, Oscar ; Artschwager, Richard ; Pettibon, Raymond ; Coffey, Susanna ; Bok, Gideon ; Yokose, Hiro ; Fink, Aaron ; Besemer, Linda ; Hirschhorn, Thomas ; Fontcuberta, Joan ; Ballester, José Manuel ; Xu Bing ; Zhu, Jinshi ; Wenda, Gu ; Smith, Ray ; Duff, John ; McCarthy, Catherine ; Saar, Lezley ; Kelly, Ellsworth ; Diebenkorn, Richard ; Saville, Jenny ; Muñoz, Juan ; Schütte, Thomas ; Kim, Tschang-Yeal ; Eliasson, Olafur ; Linnenbrink, Markus ; Wessel, Henry ; Höfer, Candida ; Zwakman, Edwin ; Rielly, James ; Uglow, Euan ; Fry, Anthony ; Hollingsworth, Dennis ; Cragg, Tony (Anthony) ; Rio Branco, Miguel ; Hernández-Diez, José Antonio ; Tompkins, Michael ; Thiebaud, Wayne ; Capilonch, Biel ; Noland, Kenneth ; Venet, Bernar ; Gerber, Gaylen ; Nelson, Joan ; Criqui, Stven ; Viola, Bill ; Tomaselli, Fred ; Bourdeau, Robert ; Newdick, Lori ; Fisher, Vernon ; Arnoldi, Charles ; Hamilton, Richard ; Opie, Julian ; Sanchez, Pauline Stella ; Eyre, Janieta ; Darboven, Hanne ; Odenbach, Marcel ; Tuttle, Richard ; LeWitt, Sol ; Lawrence, Jacob ; Bates, David ; Andre, Carl ; Apfelbaum, Polly ; Outerbridge, Paul ; Kertesz, André ; Siskind, Aaron ; Huberland, Morris ; Hartnett, Susan ; Klein, Yves ; Hollowell, David ; Rickey, George ; Torres-Garcia, Joaquin ; Gurvich, José ; Voelker, Cornelius ; Lehanka, Marko ; Kelly, Robert ; Fleming, Linda ; Roberts, Holly ; Ernst, Elisabeth ; Serrano, Laura ; Canero, Aurora ; Porter, Liliana ; Bandera, Nono ; Scherman, Tony ; Spaans, Jean Marc ; Riesebrodt, Brigitte ; Hanke, Jens ; Lemmers, Christian ; Tansey, Mark ; Karsh, Yousuf ; etc.
This catalogue is dedicated to the memory of Marcantonio Vilaça
Engels
Art Chicago 2000, Festival Hall at Navy Pier Chicago, Thomas Blackman Associates Chicago, 12.05 - 15.05.2000
boek